HISTORY TO THE STUDY OF ECTOMYCORRHIZAL FUNGI OF ARMENIA (FAMILY RUSSULACEAE) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
In this article the data of distribution and the study of ectomycorrhizal fungi from family Russulaceae, detected in Armenia are summarized. The paper presents both historical information on the studies of these species and the results of mycological studies of recent years.
Keywords: Agarical basidiomycetes, ectomycorrhizal fungi, family Russulaceae, plant associations